Visual C♯ 2010 recipes : a problem-solution approach - Jones, Allen (Expert's voice in C#., 2010)
"When you are facing a Visual C♯ 2010 problem, this book likely contains a recipe that provides you with the solution-or at least points you in the right direction. Even if you are simply looking to broaden your knowledge of the .NET Framework class library, then Visual C♯ 2010 Recipes is the perfect resource to assist you"--Resource description page